Is There Material Liability of Workers and Employees as a Type of Legal Liability in Contemporary Russian Law and Legislation? - Vladimir Valentinovich Kozhevnikov (SIASAT, 2021)
The subject of this article is the social relations regulated by the legal institution of material responsibility of workers and employees. The purpose of the article is the argumentation of the position according to which material liability does not have the status of legal liability. To achieve this goal, the following tasks were implemented: 1) the positions of the overwhelming number of supporters - theorists of law and scientists of labor law - were considered - recognition of material responsibility as one of the types of legal responsibility, along with criminal law, administrative law, etc., which is interpreted as compensation for harm caused to a worker or employee to an enterprise (organization, institution): 2) the views of scientists (Anatoly Borisovich Vengerov, Mikhail Mikhailovich Rassolov, Magomed Imranovich Abdulaev), who do not recognize material responsibility as a type of legal responsibility, have been analyzed; 3) analyzed approaches to understanding legal responsibility; 4) the author's position of understanding legal responsibility and its signs is given, focusing on such as the onset of negative consequences, imposing new additional duties on the offender; 5) the problem of correlation of legal liability measures and protection measures is considered. In conclusion, it is concluded that the identification of measures of legal responsibility and measures of protection have led, first, to an incorrect definition of civil liability, with which material liability is often compared; secondly, the controversial allocation of both the legal function of legal responsibility and material responsibility as a kind of legal responsibility, which, despite its consolidation in labor legislation, in our opinion, in its essential and substantive characteristics refers to protection measures. The scientific article also emphasizes that the problem of distinguishing between legal liability and protection measures is extremely important for law enforcement entities, who must adequately understand what measures of state-legal coercion they apply, which thereby realize their goals. At the same time, they should keep in mind that in practice the named types of state legal coercion are often applied simultaneously (for example, a civil suit in criminal proceedings).